Program Khusus Akademi Anti Korupsi untuk Pemasaran Sosial Anti Korupsi oleh Indonesia Corruption Watch (ICW) - Aditya Hammam Ramdhani (Epistemik Press, 2020)
This study describes the social marketing process of anti-corruption education through the special program of the Anti-Corruption Academy by Indonesia Corruption Watch (ICW). The problem of corruption that occurs massively creates social problems in society, so that preventive action is needed in eradicating corruption, one of which is through anticorruption education. This study discusses the social marketing of the Anti-Corruption Academy using the theory of Philip Kotler and Roberto (1989) in (Hendra, 2017) regarding social marketing products, target audiences, the core elements of social marketing, social marketing processes and evaluation of social marketing programs. The research method used is descriptive qualitative research methods. The results of this study indicate that the anticorruption social marketing process through the Anti-Corruption Academy Special Program by ICW has gone through a series of stages of the social marketing process according to Philip Kotler's theory. This can be seen through the five main components of social marketing.